DEGREE OF AGILITY IN A HOSPITAL SUPPLY CHAIN – A CASE STUDY - Martins, A.; Crespo de Carvalho, J. (9th International Symposium on Logistics, 2004)
Agility and agile supply chain are increasingly mentioned in literature. Several measurement models have been attempted but no stabilised evaluation model has been reached. The purpose of this paper is to develop a dynamic model to analyse agility performance and classify strategies according to the level of importance given to each basic dimension. Literature review on the main four agile dimensions is performed. A measurement scale is identified and is the basis to define and characterize underperforming behaviours. A services supply chain is used to test the model. Findings show that the maximum performance in terms of agility is unreachable, thus the need to continuously adjust to changes in environment.